1993
DOI: 10.1128/jb.175.20.6562-6570.1993
|View full text |Cite
|
Sign up to set email alerts
|

A cdc-like autolytic Saccharomyces cerevisiae mutant altered in budding site selection is complemented by SPO12, a sporulation gene

Abstract: LYT1 is an essential gene for the growth and morphogenesis of Saccharomyces cerevisiae. A detailed characterization of mutants carrying the lytJ-J allele showed that this mutation was recessive and pleiotropic, affecting both mitotic and meiotic functions. At the nonpermissive temperature of 37°C, lyti haploid strains budded at a distal position (instead of an axial one, as in wild-type haploid strains) and underwent autolysis when the buds were almost the size of the mother cells. These mitotic alterations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The following evidence, along with the results obtained in this study, further implies the genetic interactions among TEMI, CDC15, LTE1, DBF2, and CDC5: (i) a high dose of SP012 suppressed teml-3, Itel, dbf2-1, and lytl-l (22,27,36); (ii) overexpression of CDC15 suppressed teml-3, dbf2-1, lytl-1, and cdc5-1 (15,22,36); (iii) multiple copies of CDC5 suppressed dbf2-1 and cdc15-1 (15); and (iv) multiple copies of TEM1 suppressed dbf2-2 (36). Assuming that Teml functions upstream of Cdc15, our results strongly support the presence of a cascade consisting of GTP-binding protein (Teml) and kinases (Cdcl5, Cdc5, and Dbf2) acting to terminate mitosis.…”
Section: [-Y-35s]gtp the Gst-teml Fusion Protein Bound [Y-35s]gtp mentioning
confidence: 88%
See 2 more Smart Citations
“…The following evidence, along with the results obtained in this study, further implies the genetic interactions among TEMI, CDC15, LTE1, DBF2, and CDC5: (i) a high dose of SP012 suppressed teml-3, Itel, dbf2-1, and lytl-l (22,27,36); (ii) overexpression of CDC15 suppressed teml-3, dbf2-1, lytl-1, and cdc5-1 (15,22,36); (iii) multiple copies of CDC5 suppressed dbf2-1 and cdc15-1 (15); and (iv) multiple copies of TEM1 suppressed dbf2-2 (36). Assuming that Teml functions upstream of Cdc15, our results strongly support the presence of a cascade consisting of GTP-binding protein (Teml) and kinases (Cdcl5, Cdc5, and Dbf2) acting to terminate mitosis.…”
Section: [-Y-35s]gtp the Gst-teml Fusion Protein Bound [Y-35s]gtp mentioning
confidence: 88%
“…Moreover, these genes commonly interact with the SP012 gene. SP012, identified as a gene essential for sporulation (19), was isolated by its ability to suppress dbf2-1 (27) or lytl-l (22). We isolated the SP012 gene as a multicopy suppressor of teml-3 and cdcl5 (36) and found that the Itel disruption was also complemented by SP012 on a multicopy vector (36).…”
Section: [-Y-35s]gtp the Gst-teml Fusion Protein Bound [Y-35s]gtp mentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of genes, encoding regulatory proteins, that, when mutated, cause a cell cycle arrest similar to mob1 mutants. There is an extensive array of genetic interactions linking them together, suggesting that they belong to a common pathway (Pringle and Hartwell, 1981;Wickner et al, 1987;Johnston et al, 1990;Parkes and Johnston, 1992;Kitada et al, 1993;Molero et al, 1993;Spevak et al, 1993;Keng et al, 1994;Shirayama et al, 1994aShirayama et al, , 1994bShirayama et al, , 1996Toyn and Johnston, 1994). We have begun to establish that MOB1 shares genetic interactions with several members of this class of genes.…”
Section: Discussionmentioning
confidence: 99%
“…The S. cerevisiae strains used in the library screening and complementation assays were: L2C24d (cdc15-lyt1 ura3-52 MATa) (Molero et al, 1993); RH1779 (cdc14-1 ade2 his4 leu2 MATa) and L119-7d (dbf2 ura3-52 trp1+2 ade1 MATa), kindly supplied by Dr C. Kuhne; EO156 (tem1-3 ura3-52 leu2 his3 trp1) a gift from Dr A. Toh-e; 15DAU (cdc14-1 ura3 leu2 trp1 MATa), provided by Dr A. Bueno; 4955-3a (cdc16 his7 leu2 ura3 MATa) and 4086-23-2a (cdc23 his7 leu2 ura3 MATa) supplied by Dr M. Yuste; and WY46 (tem1::GAL-UPL-TEM1/Trp1 bar::hisG ade2-1 can1-1 his3-11, -15 leu2-3,-12 trp1-1 ura3-1 MATa) a gift from Dr R. J. Deshaies. The Candida albicans strains used were 1001 (Navarro-García et al, 1995) and CAI4 (Fonzi and Irwing, 1993).…”
Section: Strains Media and Culture Conditionsmentioning
confidence: 99%